Oral immunogenicity of the plant derived spike protein from swine-transmissible gastroenteritis coronavirus - Gómez, N. (Arch Virol, 2000)
Transgenic plants represent an inexpensive alternative to classical fermentation systems for production of recombinant subunit vaccines. Transgenic potato plants were created that express the N-terminal domain of the glycoprotein S (N-gS) from Transmissible gastroenteritis coronavirus (TGEV), containing the major antigenic sites of the protein. Extracts from potato tubers expressing N-gS were inoculated intraperitoneally to mice, and the vaccinated mice developed serum IgG specific for TGEV. Furthermore, when potato tubers expressing N-gS were fed directly to mice, they developed serum antibodies specific for gS protein, demonstrating the oral immunogenicity of the plant derived spike protein from TGEV.